Between Aesthetics and Politics: Narrative Review of Sociopolitical Functions of Art - Hermansyah, Kusen Dony (Harmonia : Journal of Music and Arts, 2024)
This narrative review explores how contemporary art criticism and cultural studies intersect to illuminate sociopolitical narratives within global artistic practices. The study aims to analyze how art functions as both an aesthetic form and a medium of political engagement, focusing on themes of critique, identity, commodification, and memory. A systematic literature search was conducted using Scopus, Web of Science, and Google Scholar, employing keywords such as art criticism, cultural studies, sociopolitical narratives, contemporary art, and identity politics. Inclusion criteria prioritized peer-reviewed works from 2000 to 2025 addressing sociopolitical contexts in art. The analysis revealed four dominant themes. First, art serves as a medium of political critique, providing platforms for resistance and public dialogue in contexts ranging from Kazakhstan to Mexico. Second, art mediates ideology and identity, reflecting tensions shaped by migration, gender, and globalization. Third, the global art market plays a paradoxical role by both enabling and constraining critical voices, often subordinating cultural meaning to economic value. Fourth, spectral theory offers insight into how art engages with trauma and collective memory across diverse cultural contexts. These findings highlight the influence of systemic political and economic forces on art while affirming its potential as a catalyst for dialogue and transformation. Policy support, educational integration, and digital innovation are identified as key strategies to strengthen art’s critical role. Future research should expand cross-cultural comparisons and explore digital methodologies to address current gaps. The review underscores art’s continuing relevance as a vehicle for sociopolitical critique in a globalized world.